2018
DOI: 10.5539/ass.v14n8p76
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Customers' Satisfaction on the Effect of CRM on Long-Term Customers Loyalty in the Banking Sector in the Palestinian Territory

Abstract: This study aims to investigate the mediating role of customers' satisfaction on the effect of customer relationship management on long-term customers' loyalty in the banking sector in the Palestinian Territory. Using advanced statistical methods. This study supports that there is a high level in implementing the CRM, customers' satisfaction, and long-term customers' loyalty. It showed that these three variables: CRM, customers' satisfaction, and long-term customers' loyalty have a significant role on the Banki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…However, any other study found the different result that no role for customer satisfaction as mediating in enhancing the impact of CRM on long-term customer loyalty in Palestinian local bank [32].…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 82%
“…However, any other study found the different result that no role for customer satisfaction as mediating in enhancing the impact of CRM on long-term customer loyalty in Palestinian local bank [32].…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 82%
“…The significant gap in the literature on this topic remains ripe for investigation (AlQershi et al ., 2018; Al-Nashmi and Al-Kholidy, 2016). The majority of works dedicated to CRM in the Middle East are limited to the service sector, for example Iriqat and Daqar (2018); Jaber and Simkin (2017) and Khasawneh and Abu-Shanab (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding customers' demands, satisfying them and, thus, retaining customers is one of these critical aspects (Sin et al, 2005). Furthermore, according to Iriqat and Daqar (2018), CRM, customer satisfaction and enduring customer loyalty play a vital role in the banking industry because customer loyalty is a core basis of current business practices and a primary spotlight of organizational strategy, in connection with Bowen and McCain (2015). The authors further emphasized that a little increase in loyal customers can result in a significant rise in profitability.…”
Section: Relation Between Customer Loyalty and Competitive Advantagementioning
confidence: 99%